2020
DOI: 10.3390/cancers12041035
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib Based Treatment Strategies in the Management of Relapsed/Refractory Multiple Myeloma with Extramedullary Disease

Abstract: Published experience with carfilzomib in patients with relapsed/refractory multiple myeloma (RRMM) and extramedullary disease (EMD) is still limited. The current study aimed to assess the efficacy and safety of carfilzomib containing therapy regimens in EMD. We retrospectively analyzed 45 patients with extramedullary RRMM treated with carfilzomib from June 2013 to September 2019. The median age at the start of carfilzomib was 64 (range 40-80) years. Twenty (44%) and 25 (56%) patients had paraosseous manifestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 47 publications
0
21
0
1
Order By: Relevance
“…Also, progression of plasmacytomas despite good BM and serological response in patients receiving thalidomide has been reported 88–90,92 . These phenomena have also been observed with bortezomib 83 and carfilzomib 85 …”
Section: Treatment Approachmentioning
confidence: 83%
See 1 more Smart Citation
“…Also, progression of plasmacytomas despite good BM and serological response in patients receiving thalidomide has been reported 88–90,92 . These phenomena have also been observed with bortezomib 83 and carfilzomib 85 …”
Section: Treatment Approachmentioning
confidence: 83%
“…Bortezomib seems to be of benefit in patients with PS disease with less evidence for EMD involvement 81–83 . Carfilzomib showed limited efficacy in relapsed patients with MM and plasmacytomas, particularly in those with EMD disease 84,85 . The efficacy of ixazomib is unknown.…”
Section: Treatment Approachmentioning
confidence: 99%
“…So erzielt die Induktionstherapie mit dem CD38-gerichteten Antikörper Daratumumab in Vierfachkombination mit Bortezomib, Dexamethason und Thalidomid bzw. Lenalidomid ein progressionsfreies Überleben ("progression free survival" [PFS]) von über 90 % nach 18 [1] bzw. 24 Monaten [2].…”
Section: Status Quo Und Therapeutische Herausforderungen Beim Multiplen Myelomunclassified
“…A recent updated meta-analysis of 20 studies demonstrated a pooled ORR of 84% with 43% complete remission (CR) in patients with heavily pretreated RRMM who had received BCMA directed CAR T cell (10). Importantly, even the heavily pretreated patients with extramedullary disease (EMD), a high risk feature, presented a high ORR of 78%, which could not be achieved by conventional combination chemotherapies such as "VDT-PACE" (bortezomib, dexamethasone, thalidomide, cisplatin, doxorubicin, cyclophosphamide, and etoposide) (34), "DexaBEAM" (dexamethasone, carmustine, etoposide, cytarabine, and melphalan) (35), daratumumab (36) or carfilzomib containing treatments (37). However, as reported by Gagelmann et al, synthesized results of five full publications from China or the United States (38-42) yielded a relapse rate of 45% at the last follow up, and the median progressionfree survival (PFS) was only 10 months (10).…”
Section: Overview Of Car T Cell Therapy For Multiple Myelomamentioning
confidence: 99%